2018
DOI: 10.1136/bjophthalmol-2017-311774
|View full text |Cite
|
Sign up to set email alerts
|

Association of low birth weight with myopic refractive error and lower visual acuity in adulthood: results from the population-based Gutenberg Health Study (GHS)

Abstract: Our data demonstrated that low BW is linked to visual acuity and refractive long-term outcomes long after childhood. Individuals with low BW are more likely to have lower visual acuity and a higher myopic refractive error in adulthood. Adults with high BW are more likely to have a more hyperopic refractive error.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
39
2
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 30 publications
(52 citation statements)
references
References 41 publications
(30 reference statements)
5
39
2
3
Order By: Relevance
“…The birth weight data distribution of our cohort was compared to distributions reported in medical literature and governmental data. 14,22 Poisson regression analysis was performed assessing the association of the different birth weight groups (birth weight <2500 g, birth weight between 2500 and 4000 g, birth weight >4000 g) with the binary variables AMD, early AMD, late AMD, and incident AMD. In model 1, the main outcome measures were tested in a univariate analysis with birth weight as independent variable; in model 2 these measures were adjusted for age (years) and sex (female); in model 3 adjustments for age (years), sex (female), SES, smoking (yes), arterial hypertension (yes), BMI (kg/m 2 ), refraction (spherical equivalent in diopter), lowdensity lipoprotein (mg/dL), high-density lipoprotein (mg/dL), and triglycerides (mg/dL) were performed, as reported in medical literature.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The birth weight data distribution of our cohort was compared to distributions reported in medical literature and governmental data. 14,22 Poisson regression analysis was performed assessing the association of the different birth weight groups (birth weight <2500 g, birth weight between 2500 and 4000 g, birth weight >4000 g) with the binary variables AMD, early AMD, late AMD, and incident AMD. In model 1, the main outcome measures were tested in a univariate analysis with birth weight as independent variable; in model 2 these measures were adjusted for age (years) and sex (female); in model 3 adjustments for age (years), sex (female), SES, smoking (yes), arterial hypertension (yes), BMI (kg/m 2 ), refraction (spherical equivalent in diopter), lowdensity lipoprotein (mg/dL), high-density lipoprotein (mg/dL), and triglycerides (mg/dL) were performed, as reported in medical literature.…”
Section: Discussionmentioning
confidence: 99%
“…Every participant was asked at the invitation to the study examination to review his or her records and family album for documentation of birth weight as reported earlier. 13,14 Participants were divided into the three birth weight groups: low birth weight <2500 g (group 1); normal birth weight with birth weight between 2500 and 4000 g (group 2); and high birth weight >4000 g (group 3) in accordance with medical literature. 15,16 Additionally, participants with birth weight below 1000 g and above 6000 g were excluded, as these self-reported data were suspected to be unreliable.…”
Section: Birth Weightmentioning
confidence: 99%
See 1 more Smart Citation
“…The participants were asked to review their records or family albums for documented birth weights; based on this information, they were divided into the following birth weight groups: group 1, low birth weight (<2500 g); group 2, normal birth weight (2500-4000 g); and group 3, high birth weight (>4000 g), as reported earlier. [16][17][18][19] Additionally, participants with birth weights below 1000 g and above 6000 g were excluded, as these self-reported data were suspected to be unreliable.…”
Section: Birth Weightmentioning
confidence: 99%
“…No association between BW and refractive error was found in 12 to 15 year-old adolescent participants in the US National Health and Nutrition Examination Survey (NHANES), although BW was associated with corneal curvature [11]. In adult participants from the population-based 1958 British Birth Cohort [15], myopia was associated with lower BW for gestational age (OR=0.90, P<0.05) and in the populationbased Gutenberg Health Study [16], refractive error was -0.017 D (95% CI -0.011 to -0.023; P<0.001) more myopic per standard deviation reduction in BW.…”
Section: Introductionmentioning
confidence: 98%